(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
The porous Silk Fibroin (SF) scaffolds crosslinked by Genipin (GP) were prepared by freeze-drying. The different amount of GP were added in different concentrations of SF solutions. Compared to the uncross- linked porous SF scaffolds, the GP crosslinked scaffolds were insoluble and showed uniform pores and porosity. The SF scaffolds, with average pore size 39-167 μm and porosity 49-71%, could be obtained by changing concentrations of fibroin solution, When the concentration of fibroin increased, the pore size diminished. The fourier transform-infrared (FT-IR) results revealed that GP could react with the -NH2 groups on the side chains of SF macromolecules to form inter- and intro-molecular covalent bonds. The FT-IR, X-ray Diffraction (XRD) and Differential Scanning Calorimetry (DSC) results also showed that the crystallinity of SF scaffold crosslinked by GP was increased slightly while the thermal stability was improved. This new fabrication way provided the basis theory for producing scaffolds with reasonable structure.